Cold-Induced Physiological and Biochemical Alternations and Proteomic Insight into the Response of Saccharum spontaneum to Low Temperature - Zhang, Bao-Qing; Huang, Yu-Xin; Zhou, Zhong-Feng; Zhou, Shan; Duan, Wei-Xing; Yang, Cui-Fang; Gao, Yi-Jing; Zhang, Ge-Min; Song, Xiu-Peng; Zhang, Xiao-Qiu; Li, Ao-Mei; Huang, Dong-Liang; et al. (International journal of molecular sciences, 2022)
Sugarcane, a cash crop, is easily affected by low temperature, which results in a decrease in yield and sugar production. Breeding a new variety with cold tolerance is an essential strategy to reduce loss from cold stress. The identification of germplasms and genes/proteins with cold tolerance is a vital step in breeding sugarcane varieties with cold tolerance via a conventional program and molecular technology. In this study, the physiological and biochemical indices of 22 genotypes of S. spontaneum were measured, and the membership function analysis method was used to comprehensively evaluate the cold tolerance ability of these genotypes. The physiological and biochemical indices of these S. spontaneum genotypes showed a sophisticated response to low temperature. On the basis of the physiological and chemical indices, the genotypes were classified into different cold tolerance groups. Then, the high-tolerance genotype 1027 and the low-tolerance genotype 3217 were selected for DIA-based proteomic analysis by subjecting them to low temperature. From the four comparison groups, 1123, 1341, 751, and 1693 differentially abundant proteins (DAPs) were identified, respectively. The DAPs based on genotypes or treatments participated in distinct metabolic pathways. Through detailed analysis of the DAPs, some proteins related to protein homeostasis, carbohydrate and energy metabolism, amino acid transport and metabolism, signal transduction, and the cytoskeleton may be involved in sugarcane tolerance to cold stress. Furthermore, five important proteins related to cold tolerance were discovered for the first time in this study. This work not only provides the germplasms and candidate target proteins for breeding sugarcane varieties with cold tolerance via a conventional program and molecular breeding, but also helps to accelerate the determination of the molecular mechanism underlying cold tolerance in sugarcane.